Integrated phytochemical, computational, in vitro, and in vivo evaluation of the anxiolytic potential of hamelia patens jacq. Methanolic leaf extract - Aghade, Mr. Karveer. B.; Ramchandra Waghmode, Miss.Waghmode; Jadhav, Dr. Vijay. B.; Aglawe, Dr. Sachin. B.; Jain, Dr. Nitin. P. (International Journal of Aquatic Research and Environmental Studies, 2026)
Anxiety disorders are among the most prevalent psychiatric conditions worldwide and represent a major public health concern due to their increasing incidence and associated socioeconomic burden. Although conventional anxiolytic drugs such as benzodiazepines are effective, their long-term use is often limited by adverse effects, tolerance, and dependence, highlighting the need for safer therapeutic alternatives. The present study aimed to evaluate the anxiolytic potential of the methanolic leaf extract of Hamelia patens Jacq. using an integrated in silico, in vitro, and in vivo approach. Preliminary phytochemical screening revealed the presence of flavonoids, phenolic compounds, alkaloids, glycosides, tannins, saponins, triterpenoids, and carbohydrates. Molecular docking studies against the GABAA receptor (PDB ID: 6D6T) demonstrated favourable binding interactions of the identified phytoconstituents, with apigenin exhibiting the highest binding affinity among the tested compounds. The extract also exhibited concentration-dependent GABA-transaminase inhibitory activity (IC₅₀ = 112.6 ± 3.4 μg/mL) and significant antioxidant activity in the DPPH free radical scavenging assay (IC₅₀ = 94.8 ± 2.8 μg/mL), suggesting its potential to enhance GABAergic neurotransmission and reduce oxidative stress. The anxiolytic activity was further evaluated in caffeine-induced Swiss albino mice using validated behavioural models, including the Elevated Plus Maze, Open Field Test, Y-Maze, and T-Maze. Oral administration of the methanolic extract at doses of 100, 200, and 400 mg/kg produced significant (p < 0.05–0.001) dose-dependent improvements in anxiety-related behavioural parameters compared with the negative control group. The 400 mg/kg dose exhibited anxiolytic efficacy comparable to diazepam, as evidenced by increased open-arm exploration, enhanced locomotor and exploratory behaviour, improved spontaneous alternation, and increased time spent in the goal arm. Collectively, these findings demonstrate that the methanolic leaf extract of Hamelia patens possesses significant anxiolytic activity, which may be mediated through modulation of the GABAergic system, inhibition of GABA-transaminase, and antioxidant mechanisms. The study provides scientific evidence supporting the therapeutic potential of Hamelia patens as a promising natural source for the development of novel anxiolytic agents. However, further studies on bioactive compound isolation, pharmacokinetics, chronic toxicity, and clinical evaluation are warranted to establish its therapeutic applicability.
Keywords: Hamelia patens Jacq.; anxiety; anxiolytic activity; GABAA receptor; GABA transaminase; molecular docking; DPPH assay; phytochemicals; medicinal plants.